Analisis Bahan Ajar Matematika Kelas 5 di Sekolah Dasar - Ramadan, Ananda Sinta; Unaenah, Een; Zaudah, Dessiana; Azizah, Nur; Ropidoh, Siti (Lembaga Yasin AlSys, 2022)
The purpose of this paper is to find out or describe the results of the analysis of open materials for Class V, whether they meet the requirements or characteristics of Class V students. The method we use is quantitative research. This study discusses the importance of teaching materials used in 5SD class. The mathematics teaching materials used in elementary school grade V are the book published by the Ministry of Education and Culture in the Revised Edition of 2018